Experience in the use of the drug Okomistin in pre- and postoperative in patients with cataract - S. D. Stebnev (Oftalʹmologiâ, 2014)
The actual problem of the modern ophthalmology is prevention of postoperative infectious complications. The efficacy of the drug Okomistin ® was studied in 500 patients after cataract surgery. A scheme for the use of the Okomistin in pre- and postoperative period is proposed. The results of the study showed that Okomistin was effective in the prevention of postoperative infection, including patients with local or systemic allergic reaction in their past history.